Necessary Characteristics for the Negotiating Manager in Atypical Conditions: Array - Gîdilica, Constantin (Acta Universitatis Danubius. Œconomica, 2021)
Management is the science of leading whose executor is man. The personality of the manager is studied in the works of scientists long before the substantiation of managerial theories, this fact facilitated the implementation of mechanisms related to the negotiation process. The negotiator is one of the roles played by the manager in his activity, but at the same time this role becomes more and more important in the current conditions. The negotiating manager is found in the commercial, political, social, international, mediation, etc. negotiations. The study of the characteristics of the negotiating manager appears from the conditions of changing the concepts, the conjuncture of the negotiations, the domains of negotiation, the unpredictable external environment, etc. The creation of a stereotype of the negotiating manager characteristic of the contemporary concept has become the object of the research in question. The author’s approach to the negotiator’s personality represents a new hypothesis in changing the concepts on the negotiation process in atypical contemporary conditions with unpredictable influencing factors. The author uses the Pareto Method in identifying key elements regarding the characteristics of negotiators regarding the conduct of prospective and successful negotiations. Analysing the categories of characteristics of the negotiating managers, formed over the centuries as a result of the theoretical substantiation put in the conditions of an applied research based on the questionnaire and the Pareto Method, the author identified the 2 categories based on the 20/80 principle. The author uses the Pareto Method in identifying key elements regarding the characteristics of negotiators regarding the conduct of prospective and successful negotiations. Analysing the categories of characteristics of the negotiating managers, formed over the centuries as a result of the theoretical substantiation put in the conditions of an applied research based on the questionnaire and the Pareto Method, the author identified the 2 categories based on the 20/80 principle. The author uses the Pareto Method in identifying key elements regarding the characteristics of negotiators regarding the conduct of prospective and successful negotiations. Analysing the categories of characteristics of the negotiating managers, formed over the centuries as a result of the theoretical substantiation put in the conditions of an applied research based on the questionnaire and the Pareto Method, the author identified the 2 categories based on the 20/80 principle.